SPEED BREAKER SEBAGAI PENGGERAK GENERATOR LISTRIK - Anwar, Zainuri; Elfiano, Eddy (UIR PRESS, 2020)
ABSTRACT The kinetic energy was produced by a moving vehicle can be used to generate power by using a speed breaker. The kinetic energy is converted into mechanical energy by altering a reciprocating connecting rod into rotation of flywheel, then it is transmitted to the generator in order to produce electrical energy. The purpose of this study was to determine the electrical energy generated from the crankshaft type speed breaker. Speed breaker used has 3 ramps with a maximum ramp height of 10 cm. the load and speed of vehicles passing the ramp are varied 72 kg, 82.5 kg, 88.7 kg at speeds of 5 km/h, 10 km/h, 15 km/h. The result of the study shows that a vehicle with the mass of 88,7 kg was able to generate a 19 V of electric voltage, 32 A of electric current and 486,4 Watts. That power is stored in a 12 V and 3 Ah batteries that needed 0.094 hour for charging. Keywords: Flywheel, Generator, Kinetic energy, Speed breaker ABSTRAK Energi kinetik yang dihasilkan oleh kendaraan yang bergerak dapat digunakan untuk menghasilkan daya dengan menggunakan speed breaker. Energi kinetik diubah menjadi energi mekanik dengan mengubah batang penghubung bolak-balik menjadi rotasi roda gila, kemudian ditransmisikan ke generator untuk menghasilkan energi listrik. Tujuan dari penelitian ini adalah untuk mengetahui energi listrik yang dihasilkan dari speed breaker tipe poros engkol. speed breaker yang digunakan memiliki 3 ramp dengan tinggi maksimum ramp 10 cm. beban dan kecepatan kendaraan yang melewati ramp di variasikan masing - masing 72 kg, 82,5 kg, 88,7 kg dengan kecepatan 5 km/h, 10 km/h, 15km/h. Hasil penelitian menunjukkan bahwa kendaraan dengan massa 88,7 kg mampu menghasilkan tegangan listrik 19 V, arus listrik 32 A, dan 486,4 Watt. Daya itu disimpan dalam baterai 12 V dan 3 Ah yang membutuhkan 0,094 jam untuk diisi daya. Kata kunci: Energi kinetik, Generator, Roda gila, Speed breaker